Filtering and Control of Wireless Networked Systems - Zhang, Dan.; Wang, Qing-Guo.; Yu, Li.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This self-contained book, written by leading experts, offers a cutting-edge, in-depth overview of the filtering and control of wireless networked systems. It addresses the energy constraint and filter/controller gain variation problems, and presents both the centralized and the distributed solutions. The first two chapters provide an introduction to networked control systems and basic information on system analysis. Chapters (3-6) then discuss the centralized filtering of wireless networked systems, presenting different approaches to deal with energy efficiency and filter/controller gain variation problems. The next part (chapters 7-10) explores the distributed filtering of wireless networked systems, addressing the main problems of energy constraint and filter gain variation. The final part (chapters 11-14) focuses on the distributed control of wireless networked systems. <In view of the rapid deployment and development of wireless networked systems for communication and control applications, the book represents a timely contribution and provides valuable insights, useful methods and effective algorithms for the analysis and design of wireless networked control systems. It is a valuable resource for researchers in the control and communication communities .
Introduction -- Fundamentals -- H∞ ﬁltering with time-varying transmissions -- H∞ ﬁltering with energy constraint and stochastic gain variations -- H∞ Filtering with Stochastic Signal Transmissions -- H∞ ﬁltering with stochastic sampling and measurement size reduction -- Distributed ﬁltering with communication reduction -- Distributed ﬁltering with stochastic sampling -- Distributed ﬁltering with random ﬁlter gain variations -- Distributed ﬁltering with measurement size reduction and ﬁlter gain variations -- Distributed control with controller gain variations -- Distributed control with measurement size reduction and random fault -- Distributed control with communication reduction -- Distributed control with event-based communication and topology switching.
Keywords: Control engineering; Telecommunication; Control and Systems Theory; Communications Engineering, Networks